2011
DOI: 10.1111/j.1369-1600.2011.00326.x
|View full text |Cite
|
Sign up to set email alerts
|

Different alcohol exposures induce selective alterations on the expression of dynorphin and nociceptin systems related genes in rat brain

Abstract: Molecular mechanisms of adaptive transformations caused by alcohol exposure on opioid dynorphin and nociceptin systems have been investigated in the rat brain. Alcohol was intragastrically administered to rats to resemble human drinking with several hours of exposure: water or alcohol (20% in water) at a dose of 1.5 g/kg three times daily for 1 or 5 days. The development of tolerance and dependence were recorded daily. Brains were dissected 30 minutes (1- and 5-day groups) or 1, 3 or 7 days after the last admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 45 publications
4
46
0
Order By: Relevance
“…Intracranial peptide administration completely abolished somatic signs associated with acute withdrawal, while the expression of anxiety measured one week after termination of ethanol exposure (protracted withdrawal) was markedly reduced (Economidou et al, 2011). Paradoxically, in another study in Sprague-Dawley rats, acute ethanol intoxication (1 day binge exposure), ethanol dependence (5 day binge exposure), and ethanol withdrawal (1 day after 5 day binge exposure) were associated with significant increases in pronociceptin mRNA levels in the amygdala (D’Addario et al 2013). Perhaps the increase in pronociceptin transcript reflects an allostatic process, or the body’s attempt to adapt to and counter the high levels of ethanol administered in that study.…”
Section: Drug Addictionmentioning
confidence: 99%
“…Intracranial peptide administration completely abolished somatic signs associated with acute withdrawal, while the expression of anxiety measured one week after termination of ethanol exposure (protracted withdrawal) was markedly reduced (Economidou et al, 2011). Paradoxically, in another study in Sprague-Dawley rats, acute ethanol intoxication (1 day binge exposure), ethanol dependence (5 day binge exposure), and ethanol withdrawal (1 day after 5 day binge exposure) were associated with significant increases in pronociceptin mRNA levels in the amygdala (D’Addario et al 2013). Perhaps the increase in pronociceptin transcript reflects an allostatic process, or the body’s attempt to adapt to and counter the high levels of ethanol administered in that study.…”
Section: Drug Addictionmentioning
confidence: 99%
“…It was reported that Dyn mRNA levels in the central nucleus of amygdala were increased after acute withdrawal from multiple alcohol "binge" administrations in rats (D'Addario et al, 2013). The central nucleus of amygdala is a critical brain region mediating anxiety-related behavior, and is a likely site for the interaction of the dynorphin and alcohol, although few studies have explored this interaction.…”
Section: Section IV Dynorphin and Kappa Opioid Receptor Stress Respomentioning
confidence: 99%
“…Targeting KORs with U50,488 blocks the rewarding effects of ethanol during conditioning, importantly, this was seen with sub-anxiogenic doses of the KOR agonist (Logrip et al 2009). Mice lacking KORs show decreased alcohol self-administration (Kovacs et al 2005), and alcohol self-administration leads to an upregulation of dynorphin in the central amygdala, a region of the extended amygdala (D'Addario et al 2013). Mice lacking dynorphin show increased alcohol preference; however, in contrast to control littermates, they do not show increased alcohol consumption following a mild stressor (Racz et al 2013).…”
Section: Behaviormentioning
confidence: 99%